#### Answer

$10x^5y^2$

#### Work Step by Step

$7x^5y^2- (-3x^5y^2) = (7 - (-3))x^5y^2 = (7 +3)x^5y^2 =10x^5y^2$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$10x^5y^2$

$7x^5y^2- (-3x^5y^2) = (7 - (-3))x^5y^2 = (7 +3)x^5y^2 =10x^5y^2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.